Redimensionamiento y automatización de la máquina de taladrado y roscado de piezas modelo Diedesheim LSA-4 para la empresa FV - Almeida Bermeo, Diego Alejandro (2012)
The activities of the company "FV-Franz Viegener Area Andina S.A." is the manufacture and sale of faucets, being currently the industry leader of Ecuador and other Latin American markets. The manufacture of faucet requires several processes, among which is the drilling and tapping of metal parts, which is done through different machines lathe section located in the "Factory Taps." Within the machinery for drilling and tapping, the machine is operating rotary DIEDESHEIM LSA-4, German and fully operational since 1980, the machine runs on three rotating shifts throughout the production. Due to years of life and daily working time, the machine had some problems in the control system, including highlighting the low efficiency and reliability, which caused the stoppage of the process. Given the facts presented, we propose and implement the design of a new control system through downsizing and automation of the machine in order to reduce downtime and maintenance costs of electricity, as well as increase productivity with the inclusion of a new mode of operation. The downsizing and automation devices involves the use of latest technology at industrial level, as reflected by the use of a programmable logic controller (PLC), human machine interface (HMI), adjustable frequency drive (AFD), industrial communication network, inductive sensors and all the programming and monitoring software for configuring these devices. Finally, we propose a design to bring the production data of the machine with the possibility of historical and reports to all points of interest in the enterprise network by storing in a database.